Sosialisasi Pembuatan Konten, Analisis Algoritma, dan Strategi untuk Media Sosial Tahun 2025 pada Komunitas Freedive Malang - Jingga Wahyu Buana; Muhammad Sagaf; Brav Deva Bernadhi; Irwan Sukendar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This Community Service Program, conducted on August 16–17, 2025, in collaboration with the Malang Freedive Community, aimed to improve participants' abilities in digital content creation, understanding of social media algorithms, and applying underwater videography techniques. The program employed socialization, hands-on training, field mentoring, and interactive discussions as its primary methods. Activities focused on enhancing digital literacy, content development strategies aligned with algorithm preferences, and effective image capture techniques for social media. Evaluation results from 15 participants showed an increase in the average pre-test score from 57.9 to 82.3 in the post-test, reflecting an improvement of 24.4 points. More than 80% of participants were able to produce at least one publishable social media content in the form of underwater photos or videos. This improvement reflects the development of participants' understanding of personal branding, content distribution strategies, and social media algorithm mechanisms on platforms such as Instagram, TikTok, and YouTube. The program demonstrates that practice-based and community-oriented training can strengthen digital capacity and create concrete opportunities for monetization through more deliberate social media management.